Using mobile communication as a tool for national growth and development (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Mobile communication emergence has brought a whole palette of new possibilities in information sharing not only for individual development but also for national growth. New mobile information devices such as Personal Digital Assistants, Smart-phones, i-phones and the like put forward several advantages for personal assistance to the mobile users. They can present up-to-date spatial/non-spatial information in a very individual, dynamic, and flexible way for the mobile users. Mobile communication devices can provide and run many other services and applications which are aimed at presenting to the mobile users the right information in the right moment and at the right place. This improves the economics and strengthens the national growth and development. The evaluations of mobile communication development projects are required in order to have a better understand on its impact on nationsâ€™ economic, politics and social growth. The research identifies the roles of mobile communication as a means for partnering with the private and public organisations in order to provide better services and awareness for the national growth and development.Â